Faktor-Faktor Yang Mempengaruhi Peningkatan Jumlah Pembiayaan Pada Bank Muamalat Indonesia (Periode 2013-2020) - Falahuddin Falahuddin; Rani Puspitaningrum; Ahmad Fauzul Hakim Hasibuan; Firda Widyastuti (LPPM, 2022)
This study examined the factors that influence the Financing of PT. Bank Muamalat Indonesia from 2013 to 2020. This study used secondary data and analyzed the data using the multiple linear regression analysis methods with the help of Eviews 11. The results partially (t-test) indicated that Wadiah Current Account positively and significantly influenced Financing, Mudharabah Deposits negatively and significantly influenced Financing, Mudharabah Deposits positively and significantly influenced Financing, Cash positively and significantly influenced Financing. Simultaneously (f-test), Wadiah Current Account, Mudharabah Savings, Mudharabah Deposits, and Cash influenced Financing. Based on the determination test (R2), the value of Adjusted R-squared was 0.7522, which indicates that 75.22% of the dependent variable has a very significant relationship with the independent variable. Meanwhile, the remaining 24.78% was explained by other variables not included in this regression equation model. Keywords: Wadiah Current Account, Mudharabah Savings, Mudharabah Deposits, Cash, And Financing.